Modernisation of the physical education system as a factor in increasing stress resistance and developing students’ psychophysical readiness for professional work - Peshkova, N.V.; Kintyukhin, A.S.; Brusov, M.A.; Lepikhina, Yu.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to justify the need to use physical education methods to increase stress resistance and develop students’ mental and physical readiness for professional activity. Methods and structure of the study. To achieve this goal, a stress sensitivity test developed by Yu.V. Shcherbatykh was used. The study, conducted at the beginning of the academic year, involved 1st-year students studying at the following educational institutions: Medical Institute (hereinafter referred to as MI, 103 people); the Polytechnic Institute (hereinafter referred to as PI, 56 people); the Institute of Humanities and Sports (hereinafter referred to as IHS, 38 people). Results and conclusions. It has been established that there are differences in the subjective perception of increased stress associated with the start of university studies among first-year students studying in different fields. Both young men and women use constructive and destructive ways to cope with stress, which requires explanatory work and increasing the importance of physical exercise to normalise the emotional background and reduce anxiety. In the process of physical education, it is necessary to promote the formation of psychophysical readiness, taking into account the requirements of future professional activity.